Invitation à la transparence : le site web sénégalais « vos démarches administratives » - Jocelyn Pierre (Netcom)
In April 2006, was publish online the Senegalese website “Your administrative procedures” http://www.demarches.gouv.sn. Since the project began, it combines the aims related to Internet development in Senegal and objectives linked to “good governance”. Through the story of the genesis and implementation of this project, the article tries to show objective of state reform and a technical means (Web) to get there. Even if it is too early to assess extent of changes made to public agents, leaders and citizens, the article focuses on the impacts already visible from the construction site. At least, the process of collecting and writing information has created among ministries agents involved in the project the beginning of a dynamic transparency to the citizen and awareness of a certain administrative complexity. It broke some administrative “routine” and down significantly some services.